Introduction to aircraft aeroelasticity and loads - Wright, Jan R.; Cooper, Jonathan E. (Chichester, West Sussex, England : Wiley, 2014)
Introduction to Aircraft aeroelasticity and Loads, SecondEdition is an updated new edition offering comprehensivecoverage of the main principles of aircraft aeroelasticity andloads. For ease of reference, the book is divided into three partsand begins by reviewing the underlying disciplines of vibrations, aerodynamics, loads and control, and then goes on to describesimplified models to illustrate aeroelastic behaviour and aircraftresponse and loads for the flexible aircraft before introducingsome more advanced methodologies. Finally, it explains howindustrial certification requirements for aeroelasticity and loadsmay be met and relates these to the earlier theoretical approachesused. Key features of this new edition include: -Uses a unified simple aeroelastic model throughout thebook -Major revisions to chapters on aeroelasticity -Updates and reorganisation of chapters involving FiniteElements -Some reorganisation of loads material -Updates on certification requirements -Accompanied by a website containing a solutions manual, andMATLAB and SIMULINK programs that relate to the modelsused -For instructors who recommend this textbook, a series oflecture slides are also available Introduction to Aircraft aeroelasticity and Loads, SecondEdition is a must-have reference for researchers andpractitioners working in the aeroelasticity and loads fields, andis also an excellent textbook for senior undergraduate and graduatestudents in aerospace engineering.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Aeroelasticity; TECHNOLOGY & ENGINEERING -- Engineering (General); Aeroelasticity; Electronic books; Electronic books